2009
DOI: 10.1002/anie.200805424
|View full text |Cite
|
Sign up to set email alerts
|

Easy Copper‐Catalyzed Synthesis of Primary Aromatic Amines by Couplings Aromatic Boronic Acids with Aqueous Ammonia at Room Temperature

Abstract: A reaction without the added extras: Aromatic boronic acids have been coupled using inexpensive aqueous ammonia to give primary aromatic amines under copper catalysis. This simple and highly efficient approach can be carried out in air at room temperature and, importantly, no base, ligand, or additive are required (see scheme).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
53
0
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 173 publications
(64 citation statements)
references
References 29 publications
7
53
0
3
Order By: Relevance
“…Aryl boron compounds are common chemicals and they are easily prepared from readily available aryl halides (such as aryl bromides and chlorides) and tosylates [14] or by iridium-catalyzed direct borylations of arenes through C À H bond activation. [15] The aryl boron compounds have been used as the starting materials to make aromatic compounds containing various functional groups (including aryl halides, [16] aryl azides, [17] aryl sulfones, [18] phenols, [19] arylamines developed by us [20] and nitroarenes [21] ) through an aerobic oxidative strategy. [22] Unfortunately, the methods need the special ligands of catalysts, organic solvents, and specific temperatures, and the limited substrate scope and unrecyclable catalyst systems greatly limit use of these methods.…”
Section: Introductionmentioning
confidence: 99%
“…Aryl boron compounds are common chemicals and they are easily prepared from readily available aryl halides (such as aryl bromides and chlorides) and tosylates [14] or by iridium-catalyzed direct borylations of arenes through C À H bond activation. [15] The aryl boron compounds have been used as the starting materials to make aromatic compounds containing various functional groups (including aryl halides, [16] aryl azides, [17] aryl sulfones, [18] phenols, [19] arylamines developed by us [20] and nitroarenes [21] ) through an aerobic oxidative strategy. [22] Unfortunately, the methods need the special ligands of catalysts, organic solvents, and specific temperatures, and the limited substrate scope and unrecyclable catalyst systems greatly limit use of these methods.…”
Section: Introductionmentioning
confidence: 99%
“…13 Amines can also be prepared from various hydroxamic acid derivatives or O-activated hydroxamic acids through Lossen rearrangement. Recently, Hoshino et al reported a novel base mediated rearrangement route for the preparation of aromatic amines without using any activating agent.…”
Section: Introductionmentioning
confidence: 99%
“…[10] Recently, copper-or palladium-catalyzed Sonogashira-type couplings of terminal alkynes with arylboronic acids/ esters, [11] or aryltrimethoxysilanes [12] have been investigated in the presence of 1-3 equivalents of Ag(I) salts as the additives. Very recently, we have developed an efficient, copper-catalyzed approach to primary aromatic amines by couplings of aromatic boronic acids with aqueous ammonia [13] via the ChanLam amination strategy. [14] Herein, we report a novel and highly efficient, copper-catalyzed synthesis of internal alkynes via aerobic oxidative arylation of terminal alkynes at room temperature.…”
Section: Introductionmentioning
confidence: 99%